Manuel de la Bárcena y Arce: una vida entre dos mundos - Pérez Vejo, Tomás (El Colegio de México, A.C., 2014)
In this study of the life and works of Manuel de la Bárcena as an expression of the challenges faced by independentist elites, the author discusses both Bárcena's changing and contradictory political and ideological positionings, and, most importantly, the rationale of his discourse, which expresses the difficult adaptation of imperial bureaucracy to a whole new time, forcing a complete change in imaginary frameworks and worldviews in the lapse of barely ten years.